The System of Mythical Symbols in The Cognitive Layer of a Literary Text - Sultan, Yesbol; Sagymbai, Zhumagul; Aituganova, Saulesh (Forum for Linguistic Studies, 2025)
This article explores the role of mythical symbols in shaping the cognitive layer of a literary text, using D. Ramazan’s short story “The Elder and the White Serpent” as a case study. Mythical symbols such as “serpent,” “water,” “elder,” and “dream” are examined not merely as artistic devices but as elements that reflect cultural memory, traditional worldviews, and cognitive frameworks. These symbols, deeply rooted in Kazakh mythology, serve as semiotic signs that encode collective knowledge and influence the reader’s interpretive process. By engaging with symbolic structures, the narrative activates culturally shared schemas, enhancing its conceptual depth. The study employs a combination of semiotic, cognitive, and intertextual analysis to reveal how these mythological elements contribute to the semantic richness of the text. The serpent is interpreted as a sacred figure associated with wisdom and protection; water is viewed as a life-giving and purifying force; the elder symbolizes ancestral knowledge; and dreams function as cognitive messages or blessings. Each symbol creates connections with cultural prototypes and intertextual sources, thereby enriching the cognitive experience of the reader. The article emphasizes that the cognitive layer of literature is constructed through symbolic encodings, which stimulate associative thinking and emotional engagement. Mythological symbols act as dynamic units that transform abstract concepts into tangible meanings. By investigating the symbolic systems embedded in the literary text, this study demonstrates how cultural and cognitive layers are intertwined, shaping both authorial intention and reader perception. Ultimately, the research highlights the relevance of cognitive literary studies in understanding the interplay between myth, language, and thought.